‘Rape Culture’ and the Rewriting of the Homeric Myth in the Works of Margaret Atwood and Madeline Miller (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The subject of the paper was the analysis of rape culture in the novella Penelopiad (2005) by Margaret Atwood and the novel Circe (2018) by Madeline Miller. ‘Rape culture’ is a term coined by feminists in the seventies of the XX century, in order to describe the climate of normalizing rape through various media, including literature, art, television and radio. Although the term ‘rape culture’ may seem like an oxymoron, we use the term ‘culture’ because the normalization of rape is perpetuated by society. After tracing the history around the term, the focus was put on the ancient times and its ever-present culture of rape. Considering that Margaret Atwood and Mаdeline Miller both chose to rewrite the myth of Odyssey, we first interpreted the original epic poem written by Homer. The second part of the paper, therefore, dealt with the analysis of rape culture in Homer’s epic and its general history as seen in ancient Greek laws, mythology, and literature. In ancient times, we revealed that not only was there quite an observable culture of rape in literature and art, but also in laws as well, especially regarding slaves and servants. Only virgin women of noble stature were somewhat protected by the law. Therefore, to the Greek audience, all the instances that we may point out as perpetuating and normalizing rape culture, would have been quite normal. Perhaps this is the very reason that a trend of rewriting ancient epics in a contemporary fashion was picked up by many authors, particularly female authors, in order to give the female characters voices they do not seem to have in their ancient versions. In the third part of the paper, we highlight the similarities and differences in the two authors’ contemporary rewritings of the observed rape culture in the epic Odyssey. Margaret Atwood, having already written a satire novella on rape, titled Rape Fantasies, is no stranger to this topic. Atwood’s novella Penelopiad is coloured with her recognizable irony, especially with having chosen Penelope as the narrator, showing her side of the story, but also the part she played as a queen, in court, pertaining to the rape of her servant maids. Madeline Miller, on the other hand, having come from a different socio-political background, gives power and voice to her female protagonist that Atwood isn’t inclined to give hers. Because of this striking difference, we also have to take into account the sociopolitical climate of the time in which the two authors wrote, due to the obvious, even though small, temporal distance that could have affected their narrative approach. We conclude that, although both Atwood and Miller show the reality and consequences of rape culture in both ancient and contemporary times, the latter still approached this narrative with more optimism, while Miller opted to show graphically the act of Circe’s rape. Atwood still maintains her recognizable style full of irony and dark humor, giving the maids a voice to tell their story at the very end, which ultimately results in no change.
Keywords: rape culture; Penelopiad; Margaret Atwood; Circe; Madeline Miller